2021
DOI: 10.1007/978-981-16-2377-6_10
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Model for Predicting Fetal Hemoglobin Levels in Sickle Cell Disease Patients

Abstract: Sickle cell disease is one of the commonest genetic diseases and is defined as a decrease in hemoglobin concentration in the blood. The main known factor that can alleviate the disease is the persistence of fetal Haemoglobin (HbF) and thus the aim of our research is to build a model to predict the HbF% of patients based on the 3 regulating genes of the disease (BCL11A, Xmm1-HBG2, HBS1L-MYB). A machine-learning approach is employed in order to improve the accuracy of the model, with various algorithms of that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Additionally, their study revealed that complete blood count (CBC) parameters were effective in discriminating between IDA and β-thalassemia for patients. Oikonomou et al [10] built a model that can predict the percentage fatal haemoglobin (HbF%) of patients. The authors explored and compared the accuracy of various machine learning algorithms like Decision Tree, Gradient Boosted Trees, Linear Regression, K-Nearest Neighbors, Neural Network, Random Forest, and Gaussian Process.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their study revealed that complete blood count (CBC) parameters were effective in discriminating between IDA and β-thalassemia for patients. Oikonomou et al [10] built a model that can predict the percentage fatal haemoglobin (HbF%) of patients. The authors explored and compared the accuracy of various machine learning algorithms like Decision Tree, Gradient Boosted Trees, Linear Regression, K-Nearest Neighbors, Neural Network, Random Forest, and Gaussian Process.…”
Section: Introductionmentioning
confidence: 99%